BIOPHYSICAL FACTORS OF FLOODING IN THE COMMUNE OF LALO - AKINDELE, Akibou Abaniché (My University, 2019)
Flooding in the Lalo Commune is increasing over time and creating real damage to the people. They transform them into "climate refugees" in their own commune. Several biophysical factors explain these floods in the Municipality of Lalo. This research presents the biophysical factors explaining the vulnerability of human settlements to floods in Lalo Commune. The approach adopted was the collection of data, their processing and the analysis of the results. Hydro-climatological data for the period 1981 to 2016 were used. The evolution of monthly rainfall regimes is known, thanks to the systemic approach that combines graphical method and frequency analysis. For 80% of respondents, precipitation is the first physical trigger of flooding in the municipality of Lalo. Then, 70% argue that the proximity of the Couffo river fields leads to a flood due to the overflow of the river (flood). Thus, the increase in river flows is considered the second most important physical factor of flooding in Lalo. In third place, it is the nature of the soil which explains the floods in the Municipality of Lalo (79% of the respondents). The lack of vegetation cover is one of the significant elements in the biophysical vulnerability factors of human settlements to floods in Lalo Commune.
Keywords: Lalo; biophysical factors; flooding